Characteristics and reference values of fat mass index and fat free mass index by bioelectrical impedance analysis in an adult population. Issue 5 (October 2019) - Jin, Meng; Du, Hanze; Zhang, Yuelun; Zhu, Huijuan; Xu, Ke; Yuan, Xianxian; Pan, Hui; Shan, Guangliang
Summary: Background & aims: We aim to examine the influence of sex, age, region and ethnicity on fat mass index (FMI) and fat free mass index (FFMI), and to establish FMI and FFMI reference values in Chinese adults. Methods: A stratified cluster sampling method was adopted to enroll Chinese participants in this cross-sectional study. Questionnaire surveys and medical examinations were performed to collect data, and body composition parameters were measured by bioelectrical impedance analysis. FMI and FFMI were calculated as the ratio of fat mass and fat free mass to the square of height. Differences in mean values for parameters were tested by Student's t -test or one-way analysis of variance. Reference values of FMI and FFMI were obtained using the percentiles method. Results: A total of 8959 multiethnic healthy Chinese adults were included in the analysis. Males had higher mean FFMI (males, 18.6 ± 1.6 kg/m 2 ; females, 15.7 ± 1.1 kg/m 2, P  < 0.001) but lower mean FMI (males, 5.1 ± 2.1 kg/m 2 ; females, 7.8 ± 2.8 kg/m 2, P  < 0.001) than did female participants regardless of age and ethnicity. For both sexes, FMI (Male: Bouyei, 4.2 ± 1.8 kg/m 2 ; Uygur, 5.8 ± 2.2 kg/m 2, P  < 0.001; Female: Bouyei, 6.7 ± 2.3 kg/m 2 ; Uygur, 9.0 ± 3.2 kg/m 2, P  < 0.001) and FFMI (Male: Bouyei, 17.8 ± 1.4 kg/m 2 ; Uygur, 19.4 ± 1.6 kg/m 2, P  < 0.001; Female: Bouyei, 15.1 ± 1.0 kg/m 2 ; Uygur, 16.3 ± 1.1 kg/m 2, P  < 0.001) were lowest in Bouyeis and highest in Uygurs. FMI and FFMI values increased with age until they peaked in the 30–39 year age group in males and after the age of 40 years in females for all ethnic groups. Reference values (5th–95th percentile) of FMI and FFMI were presented according to gender, age, region and ethnicity. Conclusion: The body composition of Chinese population differs in different age, sex, ethnicity and region subgroups. Practitioners and future studies may need to consider different reference values for FMI and FFMI in Chinese adults among Han, Bouyei and Uygur populations; these values can serve as indices for evaluating nutrition status and identifying abnormalities in body composition.